Assessing best practice for selecting surrogates and target–setting methods in a megadiverse country - Urquiza–Haas, T.; Tobón, W.; Kolb, M.; Lira–Noriega, A.; Contreras, V.; Alarcón, J.; Koleff, P. (Animal Biodiversity and Conservation, 2019)
Systematic conservation planning provides a framework to identify representative areas of biodiversity, but its effectiveness depends on the choice of surrogates and targets. Mexico has conducted participatory and comprehensive gap analyses. We present the results of two independent surrogate assessments to test the criteria used in Mexico’s spatial conservation prioritization. We tested the surrogate efficiency of range restricted, endemic, and threatened mammals and the influence of target–setting on the spatial configuration of the conservation network, as well as the performance of taxonomic–based surrogates. Results show that target–setting heavily influences the spatial configuration and irreplaceability values of the conservation area network. Representation effectiveness and coverage of species distribution was sensitive to surrogate selection but not to target–setting. Threatened and rare species were poorly represented when other surrogate species were used, while threatened mammals represented 90 % of all species. The effectiveness of networks designed for a single vertebrate taxon varied greatly; reptiles and amphibians performed better than random achieving high species representation.